Time-Delay Signature of Chaotic Vertical-Cavity Surface-Emitting Lasers with Polarization-Rotated Optical Feedback - Xiang, Shui-Ying (水英 项); Pan, Wei (讳潘); Yan, Lian-Shan (连山 闫); Luo, Bin (斌罗); Zou, Xi-Hua (喜华 部); Jiang, Ning (宁江); Wen, Kun-Hua (坤华 温) (Chinese physics letters, 2011)
To quantitatively evaluate the time-delay （TD） signatures of chaotic signals generated by vertical-cavity surface- emitting lasers （VCSELs） with polarization-rotated optical feedback （PROF）, we propose four cases of resolution coefficients R based on correlation functions. The resolution coefficient characteristics for the x-polarization （XP） mode, g-polarization （YP） mode and the total output are considered. The dependences of R on the feedback strength and feedback delay are discussed and compared carefully. The two-dimensional maps of R show that the TD signatures for the single polarization mode （i.e., XP or YP mode） are much more difficult to retrieve than those for the total output in the entire parameter space. Thus, by using single polarization mode as a chaotic carrier, the TD signatures are extremely difficult to be identified, which contributes a lot in the security-enhanced VCSELs-based chaotic optical communication systems.